Modeling and Control in Open-Channel Irrigation Systems (2021)
This thesis reviews and discusses the existent modeling, estimation, and control strategies that have been reported in the field of open channel irrigation systems (OCIS). Also, propose two control-oriented modeling strategies, which include information about potential energy balances along the channels, and the nonlinear hydraulic dynamics proper of the OCIS. Moreover, the modeling strategies are useful to describe the dynamic behavior of interacting OCIS. The proposed control-oriented modeling strategies has been used in the development of deterministic and stochastic strategies for detection isolation and magnitude estimation of unknown flows such as leaks and seepage. In the control area, the development and implementation of conventional control strategies for OCIS are explored, and a nonlinear control strategy for interacting channels is proposed. Finally, an efficient optimization-based control approach for OCIS has been developed from a nonlinear model predictive control strategy that takes advantage of the control-oriented modeling strategies accuracy, and available information of the users' demands in the development of an optimization problem with a finite horizon, which is solved at each time instant with the objective to minimize losses caused by leaks and seepage while the users demands and operational and hydraulic restrictions of the OCIS are satisfied.